The Role of International Marketing Strategies in Enhancing the Competitive Advantage A Field Study in the Ports of Lattakia and Tartous - رامي محمد; سومر ناصر; طارق ثائر عليا (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to determine the role of international marketing strategies (pricing strategy, promotion strategy, product (service) strategy, distribution strategy in enhancing the competitive advantage of the ports of Latakia and Tartous. The research adopted the descriptive approach, and the study population included all the administrative officials in the General Company for the Ports of Lattakia and Tartous, and the sample size was (150) administrative officials, where the questionnaire was distributed as the research tool to them, and (131) questionnaires were retrieved, with a response rate of .(87.33%) The results of the research found that there is a weak and significant direct relationship between international marketing strategies and indicators of competitive advantage in the ports of Lattakia and Tartous, where the changes in the indicators of competitive advantage caused by international marketing strategies amounted to (26.3%).